AJIC Issue 28, 2021 - Full Issue - (:unkn) unknown (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
Articles on social media, mobile banking apps, cyber threats, ICT intermediation, e-government IS projects, m-learning, and cybersecurity policymaking.
Articles on social media, mobile banking apps, cyber threats, ICT intermediation, e-government IS projects, m-learning, and cybersecurity policymaking.